The role of teacher code-switching and its functions in the L2 English classroom: insights into CG students' attitudes at tertiary level education - Kkese, Elena (My University, 2020)
This paper approaches code-switching (CS) from a sociolinguistic perspective aiming at investigating students’ attitudes toward teacher CS in an English-speaking classroom context. It also aims at examining the functions teacher CS fulfils in the classroom. The study was conducted at two universities in Greekspeaking Cyprus. In the light of these aims, the study involved 101 university students with a Cypriot Greek (CG) linguistic background who were asked to fill in a three-section 30-item questionnaire concerning the use of teacher CS from second language English to first language CG. Both quantitative and qualitative methods were employed to obtain data for the study. The findings indicate that students perceive teacher CS as a source of support for students’ learning process as well as a learning resource for content ensuring students’ comprehension and learning. The results are interpreted according to Halliday’s theory of pedagogical functions, which leads to the development of four categories of attitudes in relation to teacher CS. The categories involve attitudes toward teacher CS in relation to subject access, classroom management, interpersonal relations and teachers’ persona.
Keywords: Second language; Code-switching; Language attitudes; Functions; Tertiary level education